Highly Chemoselective and Regioselective Dehydrogenative Cross-Coupling Reaction between Pyridines and Ethers - Salman, Muhammad; Huang, Xing-Fen; Huang, Zhi-Zhen (Synlett, 2015)
A highly chemoselective and regioselective dehydrogenative cross-coupling (DCC) reaction of unactivated pyridines with cyclic or acyclic ethers has been developed to give the corresponding 2- or 4-coupled pyridines in satisfactory yields. The DCC reaction affords an efficient and greener synthesis for a range of new pyridines. A possible mechanism involving radical substitution is also proposed.
Keywords: dehydrogenative; cross-coupling; pyridine; ether; synthesis